A manual for self-study and individual tasks on course "Organizational behavior" - Zamula, O. V. (National Technical University "Kharkiv Polytechnic Institute", 2025)
The course ”Organizational behavior” aims to ensure that students master the specific techniques and tools for managing organizational behavior; formed skills and abilities to analyze group and intergroup dynamics in the organization.
Методичні вказівки до самостійної роботи і виконання індивідуальних завдань з дисципліни "Організаційна поведінка"
Keywords: manual; self-study; individual tasks; organizational behavior; методичні вказівки; самостійна робота; індивідуальні завдання; організаційна поведінка